1983
DOI: 10.1136/ard.42.5.575
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of collagen types and fibronectin in cartilage by immunofluorescence.

Abstract: SUMMARY Collagens type I, II, III, IV, and V and the minor cartilage collagens, la 2a 3a, C-PS 1, and C-PS 2, were purified, antibodies raised, and then used in immunofluorescence studies on bovine nasal cartilage (BNC). Punctate This report describes the localisation of these collagens in BNC by immunofluorescence.Materials and methods Collagens. These were isolated from various bovine tissues after limited pepsin digestion. Type II, la 2a 3a, C-PS 1, and C-PS 2 collagens were isolated from adult nasal cart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 18 publications
(3 reference statements)
2
28
1
Order By: Relevance
“…Immunohistochemistry confirmed the predominance of type II collagen fibers found in the cartilage ECM. This distribution has also been reported for analogous cartilages of other animals (Evans et al, 1983;Eyre et al, 1991;Morrison et al, 1996).…”
Section: Discussionsupporting
confidence: 62%
“…Immunohistochemistry confirmed the predominance of type II collagen fibers found in the cartilage ECM. This distribution has also been reported for analogous cartilages of other animals (Evans et al, 1983;Eyre et al, 1991;Morrison et al, 1996).…”
Section: Discussionsupporting
confidence: 62%
“…Type X collagen has also been identified in the fibrocartilage at the bone insertion site of the Achilles tendon (Fukuta et al 1998). Type V (Evans et al 1983;Eyre et al 1987;Bland and Ashhurst 1996) and Type VI (Sakai et al 1986;Keene et al 1988;Poole et al 1988) collagen have been reported to be present in different degrees in the three cartilage subtypes.…”
mentioning
confidence: 98%
“…Structural studies of canine (23,25), human (26), and rabbit (1 1) articular cartilages have shown middle-and deep-layer chondrocytes surrounded by a pericellular matrix and enclosed within a pericellular capsule. While the composition of the capsule is not yet known, we have previously suggested that it may contain type IX and other minor collagen species that have been immunolocalized in the pericellular microenvironment around a variety of mammalian cartilage chondrocytes (2,(13)(14)(15)23,(25)(26)(27).The chondrocyte, its pericellular matrix and capsule are thought to represent the chondron (26), a term first introduced by Benninghoff (3) to describe the functional and metabolic unit of the cell and its pericellular microenvironment (21,34). We report here on preliminary techniques for the isolation and examination of single and multiple chondrons extracted from homogenized samples of fresh and fixed canine tibial cartilage.…”
mentioning
confidence: 99%